2011
DOI: 10.1128/aac.01192-10
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the E138K Resistance Mutation in HIV-1 Reverse Transcriptase Conferring Susceptibility to Etravirine in B and Non-B HIV-1 Subtypes

Abstract: We have selected for resistance to etravirine (ETR) and efavirenz (EFV) in tissue culture using three subtype B, three subtype C, and two CRF02_AG clinical isolates, grown in cord blood mononuclear cells. Genotypic analysis was performed at baseline and at various weeks of selection. Phenotypic resistance in regard to ETR, EFV, and nevirapine (NVP) was evaluated at weeks 25 to 30 for all ETR-selected viruses and in viral clones that contained specific resistance mutations that were inserted by site-directed mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
61
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(66 citation statements)
references
References 47 publications
5
61
0
Order By: Relevance
“…We found that when present alone, the E138K, M184I, and M184V mutations each reduced the RC of HIV-1 3-to 4-fold compared to that of the WT in the absence of drug. This observation confirms and extends a previous report that found a 2-fold decrease in the RC in E138K mutants (2). In contrast, the combined presence of E138K and either M184I or M184V resulted in an RC equal to that of the WT.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…We found that when present alone, the E138K, M184I, and M184V mutations each reduced the RC of HIV-1 3-to 4-fold compared to that of the WT in the absence of drug. This observation confirms and extends a previous report that found a 2-fold decrease in the RC in E138K mutants (2). In contrast, the combined presence of E138K and either M184I or M184V resulted in an RC equal to that of the WT.…”
Section: Discussionsupporting
confidence: 81%
“…Although initial studies of in vitro selection with ETV reported a variety of resistance mutations (25), a more recent report using clinical isolates from several different HIV-1 subtypes found that the E138K mutation was selected in all isolates and was usually the first mutation to emerge (2). A number of amino acid substitutions at RT position 138, including E138K, were identified in HIV-1 after the failure of ETV in the phase 3 trials (22).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cells in 24-well tissue culture plates were infected with recombinant viral clones at a similar multiplicity of infection (MOI). Selection for viral resistance mutations was performed by using increasing concentrations of RT inhibitors at starting concentrations below the 50% effective concentration (EC 50 ), as described previously (3,38). As controls, all viruses were simultaneously passaged without drugs.…”
Section: Chemicalsmentioning
confidence: 99%